2012
DOI: 10.1093/intqhc/mzs059
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes and reducing costs by modular training in infection control in a resource-limited setting

Abstract: Standardization of infection control training and practices is the most cost-effective way to reduce HCAIs and related adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 18 publications
0
38
0
6
Order By: Relevance
“…In 2009, we recorded rates of 3–5% in maternity units [15] while others have reported infection rates of 6% [30] and 18% [31] in non-intensive care surgical settings. These figures suggest that the levels of infection we recorded are plausible.…”
Section: Discussionmentioning
confidence: 88%
“…In 2009, we recorded rates of 3–5% in maternity units [15] while others have reported infection rates of 6% [30] and 18% [31] in non-intensive care surgical settings. These figures suggest that the levels of infection we recorded are plausible.…”
Section: Discussionmentioning
confidence: 88%
“…The probabilities of reduced HAI through improved hand hygiene compliance will be retrieved from phase 1 and phase 2 of the study. Similarly cost data will be obtained from Indian studies reporting cost per HAI patient and per day of ICU stay [26,27].…”
Section: Model Inputsmentioning
confidence: 99%
“…The other two educational studies by Singh et al and Girard et al delivered face-to-face training programmes across hospital staff on geriatric units but neither study found a significant reduction in CAUTI or UTI [32,33]. Singh et al used a faceto-face training intervention in geriatric units at six locations, which covered general infection control, including hand hygiene, sterilization and disinfection, isolation precautions, etc., using didactic sessions, video shows, quizzes, role plays, and tests; despite not finding reductions in CAUTI they did find significant reductions in all other infection rates [32].…”
Section: Education And/or Training Interventionsmentioning
confidence: 99%